Germany’s Strategic Contraction Following American Hegemony in the Context of Offensive Realism Theory - Tolga Öztürk (Güvenlik Stratejileri Dergisi)
This study examines the position of the European continent within the international system, focusing specifically on Germany, from the years when the future of the global international system began to be debated following the Cold War up to the present day. Since the 1990s, there has been ongoing debate regarding whether the international system will remain dominated solely by the United States (U.S.) as a hegemon or evolve towards a multipolar world. Following the reunification of Germany after the Cold War, Europe and particularly Germany entered a new and notably economically prosperous period. This period has been characterized by the prominence of international organizations and the concept of “soft power”. The article’s research question is whether Germany’s prominence and the concepts of democracy and international cooperation in Europe are related to U.S. hegemony, and if so, which factors can explain this. Considering the current emphasis on the multipolar world and the prevalence of potential conflict areas rather than the functionality of international cooperation and institutions, the article aims to elucidate the systemic reasons for Germany’s constrictions vis-à-vis global powers and the options for alleviating this constriction by utilizing Mearsheimer’s theory of offensive realism.